Predictive modeling for clinical trial completion: assessing the phase success - factors driving predictive outcomes - Francalanci, Erica (2025)
This study investigates predictive modeling of clinical trial completion using the HINTBasic and HINTPlus models. By integrating multimodal datasets, the models predict clinical trial phase success. Additionally, the study provides interpretability insights into the HINTPlus model's decision-making process. Our findings support informed decision-making, optimize resource allocation, and accelerate drug development in clinical trials.